Characteristics of Stress Field and Damage Law of Coal Rock in Residual Pillar of Top Slice and Its Application - Wu, Fengfeng; Yu, Xin; Zhao, Gaoliang; Du, Beiju; Lv, Bo; Zhang, Jian (Frontiers in Earth Science, 2022)
This article presents a theoretical analysis and numerical simulation studies to determine the suitable position for the lower slice roadway in a residual pillar area after top slicing a thick coal seam. We considered the load concentration on the coal pillar, the goaf floor, and the stress distribution characteristics of the coal pillar area before and after the top slice. With a mechanical model built of the residual pillar load propagation in the floor and the failure model of the floor surrounding rock, the analytical formula we deduced for the coal pillar floor stress and the expression of the floor failure depth of the roadway provides a basis for the reasonable determination of the position of the lower slicing roadway. Studies proved that after mining the top slice working face, the floor stress field of the residual pillar area presented characteristics of the non-uniform distribution. The stress concentration occurred below the coal pillar. The stress variation area appeared at the edge of the coal pillar, with a stable stress area appearing far away from the coal pillar area. Therefore, the roadway layout should avoid the areas below the coal pillar and the coal pillar edge with high stress levels and a large stress variation gradient. High stress concentration formed on the coal pillar transferred to the lower layered coal and floor strata, and decreased the stress concentrations layer by layer. However, mining of the top-layered working face affected the coal, and rock mass damaged the coal pillar floor area and weakened the mechanical properties, which was not conducive to the control of the roadway surrounding rock. The research results applied to No. 30117 working face of the lower slice of the Shancheng Coal Industry, and the proper position of the return airway of the working face was determined to be 8 m outside the east side of the residual pillar in the top slice, achieving a good surrounding rock control effect.